Family support in high ability students from different socio-educational contexts - Castellanos Simons, Doris (2015)
This work aimed to analyze the perceptions of family support of school learning in 79 high intellectual ability 6th grade students from three educational contexts in Morelos, Mexico: urban (public, private) and rural indigenous schools. The students answered the SAGES-2 (Johnson & Corn, 2001) and the Family Support Questionnaire of Bazán & Domínguez (2009). Significant differences were only found between the three contexts in the perception of regular communication with teachers in Language (Spanish), which wasperceived more frequently in students from private schools, regardless of the area of abilities. This communication was perceived the least in students from rural indigenous schools. The results emphasize the importance of family and socioeconomic variables to understand the manifestation, development, and education of high ability students from different cultural contexts.